A case of Trousseau syndrome caused by pulmonary adenocarcinoma that was controlled for one year and 10 months with thrombosis treatment using an EGFR tyrosine kinase inhibitor and chemotherapy. (2015) - Masubuchi, Hiroaki; Maeno, Toshitaka; Uchida, Megumi; Kono, Shunichi; Suzuki, Masafumi; Takemura, Masao; Yamaguchi, Aya; Yamaguchi, Koichi; Kanbe, Masahiko; Kitahara, Shinsuke; Hara, Kenichiro; Hara, Shiro; et al.
Abstract: A 47-year-old female with no history of previous illnesses developed cerebral infarction and was diagnosed with lung cancer, specifically EGFR mutation-positive adenocarcinoma, and Trousseau syndrome. The patient's response to anticoagulant therapy with non-fractionated heparin was very poor; however we were able to control the thrombosis with chemotherapy. She survived for one year and 10 months following treatment with gefitinib, CBDCA + PEM and erlotinib, without recurrence of thrombosis. Trousseau syndrome carries a poor prognosis and controlling thrombosis is difficult. In this case, the administration of anticancer therapy allowed use to control the patient's thrombosis. Therefore, this case highlights the importance of treating cancer in patients with Trousseau syndrome. In addition, the FDP and D-dimer levels changed in parallel with changes in the CEA level, which suggests that the activity of cancer is related to an internal thrombotic tendency. Hence, changes in the FDP and D-dimer values are associated with the efficacy of treatment with EGFR tyrosine kinase inhibitors and chemotherapy and may function as markers of recurrence.